Exploring Primitive Legume Symbiosis Using Chamaecrista Fasciculata as a Model - (:unkn) unknown (My University, 2019)
Legumes form symbiotic associations with diazotrophs collectively termed “rhizobia” leading to the formation of nodules and N2-fixation and contribute significant amounts of fixed N to agricultural and natural environments. The mechanisms of nodulation and N2-fixation are extensively studied using model legumes that belong to the Papilionoideae, in which nodulation is widespread and advanced. In contrast, very little is known about the mechanisms of nodulation and N2-fixation in in basal Caesalpinioideae subfamily in which nodulation is rare. The nodulating caesalpiniod legume Chamaecrista fasciculata is widespread in North America and is suggested as a complementary model to study legume nodulation because of its divergence from the papilionoids nearly 60 million years ago. As a first step in understanding nodulation in basal legumes, we have isolated rhizobial strains from soils of Mid-Western USA that form N2-fixing nodules on C. fasciculata roots. Molecular phylogenetic analysis based on 16S rDNA was performed on 13 unique isolates and revealed C. fasciculata is exclusively nodulated by Bradyrhizobium spp, a group of rhizobia considered more ancient than other papilionoid nodulating rhizobial strains. Multi-locus phylogenetic analysis using ITS, nodA, nifH, recA, and dnaK was also used to further classify these unique isolates from one another. Using a GFP marker introduced in one unique isolate, as well as light microscopy and TEM, we were able to obtain a better understanding of how Bradyrhizobium spp is able to colonize and effectively nodulate in C. fasciculata. With the basic understanding of what these isolates are and how they compare to one another on a phylogenetic level, we looked at the growth promoting abilities of these isolates to determine nodulation and N2-fixing abilities of each and how they relate to one another.